Some Determinants of Classroom Psychosocial Environment in Australian Catholic High Schools: A Multilevel Analysis - Dorman, Jeffrey P. (Catholic Education: A Journal of Inquiry and Practice, 2009)
This research investigated some determinants of classroom environment in Australian Catholic high schools. The Catholic School Classroom Environment Questionnaire (CSCEQ) was used to assess seven dimensions of the classroom pyschosocial environment: student affiliation, interactions, cooperation, task orientation, order and organization, individualization, and teacher control. The sample consisted of 1,719 students from 80 classes in 20 Catholic coeducational and single-sex schools. Validation data attested to the sound structural properties of the CSCEQ. Because the data were nested (i.e., students within classes within schools), multilevel analyses were used to investigate the influence of student gender, grade, subject, and school type on students' perceptions of the classroom environment. Statistically significant associations between some of these grouping variables and some of the CSCEQ scales were evident, with gender and grade the main explanatory variables. Variance in order and organization was not explained by any of the four hypothesized grouping variables.